Explicit Knowledge and Processes From a Usage‐Based Perspective: The Developmental Trajectory of an Instructed L2 Learner. Issue 4 (15th October 2014) - Roehr‐Brackin, Karen
<x xml:space="preserve">Abstract</x> This article considers explicit knowledge and processes in second language (L2) learning from a usage‐based theoretical perspective. It reports on the long‐term development of a single instructed adult learner's use of two L2 constructions, the German Perfekt of gehen ("go, " "walk") and fahren ("go by vehicle"), which was tracked over a period of more than 3 years. The results indicate that explicit knowledge and processes seemed to have a powerful impact on the participant's L2 learning and use, apparently enabling him to override the predicted bottom‐up developmental path in certain circumstances and take a top‐down approach instead. Specifically, it was found that the development of fahren was consistent with the predicted trajectory of moving from item‐based to more schematic constructions. By contrast, the participant's use of gehen was characterized by schematic constructions almost from the beginning, suggesting a shortcut facilitated by explicit knowledge and processes. Both potential benefits and pitfalls associated with this alternative learning path are highlighted. The findings are explicated with reference to usage‐based and complexity/dynamic‐systems‐theoretic concepts, thus offering an integration of explicit knowledge and processes in L2 learning and use into this particular theoretical framework.